EVALUATION OF PHOSPHORUS AND URTICA ON GROWTH AND YIELD OF FOUR CULTIVARS PEA (PISUM SATIVUM L.) - Mohammed, Ghurbat Hassan (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2025)
This study was carried out at the vegetable research farm, College of Agricultural Engineering Sciences, Dohuk University during two growing seasons on the period from 15th November 2021to 1st May 2022 and 15th November 2022 to 1st May 2023, to study the effect of two levels of phosphorus (0 and 36 kg.ha-1) and three levels of Urtica extract (0, 3 and 6 g.l-1) on four cultivars of pea (Mammoth, Mezza Rama, Kaspa and Javor). The results showed that the Mammoth cv. significantly enhanced plant height (cm) and number of pods.plant-1 during both seasons, while Meza Rama cv. significantly enhanced chlorophyll%, weight of pod (g), length of pod (cm), width of pod (cm), number of seeds.pod-1, total yield (g.plant-1) and total yield (t.ha-1) at both study seasons. The application of 36 kg.ha-1 phosphorus caused a significant increase for the all studied parameters. In the same time the increased Urtica concentrations caused significantly increased all studies parameters at the first and second seasons except weight of pod (g), length of pod (cm) and width of pod (cm) in the second season. The dual interaction between two factors (cultivars and phosphorus), cultivars and Urtica) and (phosphorus and Urtica) significantly enhanced all parameters at both seasons. Also the triple interaction among three factors caused a significant effect for the all of the studied parameters compared control.